Extracorporeal Membrane Oxygenation in Severe Acute Eosinophilic Pneumonia - Dougherty, Sean C.; Ghaus, Sophia; Debesa, Orlando (Frontiers in Medicine, 2019)
Acute Eosinophilic Pneumonia (AEP) is a potentially fatal cause of hypoxemic respiratory failure characterized by fever, diffuse bilateral pulmonary infiltrates, and pulmonary eosinophilia. Shown to be associated with a number of environmental exposures and lifestyle choices, AEP has a good prognosis when diagnosed early and treated with corticosteroids. In this clinical case report, we detail the presentation, evaluation, diagnosis and management of a 40-year old male who presented to the emergency department with dyspnea, chills and diaphoresis. He had a history of pulmonary embolism eight years prior but was otherwise healthy, though he had re-started smoking cigarettes a week prior to presentation. Initial chest CT scan revealed widespread mixed groundglass and solid airspace opacities; over the next twelve hours, he rapidly decompensated and after not responding to other invasive mechanical ventilation, was emergently cannulated for veno-venous extracorporeal membrane oxygenation (V-V ECMO). Bronchoalveolar lavage later revealed pulmonary eosinophilia, and after an infectious workup was negative, a diagnosis of AEP was reached and the patient was started on corticosteroids. To our knowledge, this is one of few published cases of AEP requiring V-V ECMO for clinical stabilization, highlighting the utility of this treatment modality in severe disease.